Determinants of work-life balance for working mothers. - Burdhan, Wan Nur Nalisa; Abu Bakar, Hatinah; Abdullah, Zalinawati (International Journal of Accounting, Finance and Business, 2025)
In recent years, work-life balance issues especially for working mothers have become a prominent concern in the society and emphasis on work-life balance policies has emerged due to change in demographic composition of workforce. The main objective of this study is to examine the relationship between family responsibility and childcare arrangement on the work-life balance. A purposive non-probability sampling technique method was used to select the respondents. Based on the G Power calculation, this study requires a minimum sample size of 96 working mothers in Malaysia. The findings revealed that the family responsibility has a significant impact meanwhile childcare arrangement had no significant impact on the work-life balance. In addition, this study provides discussion and recommendations for the future reference that has been applied based on developed countries that could help working mothers in Malaysia to achieve the real work-life balance in harmonious way.